2020
DOI: 10.12688/gatesopenres.13116.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the power to detect a change caused by a vaccine from time series data

Abstract: When evaluating the effects of vaccination programs, it is common to estimate changes in rates of disease before and after vaccine introduction. There are a number of related approaches that attempt to adjust for trends unrelated to the vaccine and to detect changes that coincide with introduction. However, characteristics of the data can influence the ability to estimate such a change. These include, but are not limited to, the number of years of available data prior to vaccine introduction, the expected stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This information provides important supportive evidence to recommend the ongoing use of PCV in Laos. However, we were not able to do a hospital administrative review for pneumonia cases post-PCV with a PCV impact evaluation as we had insufficient power to undertake this; a simulation analysis based on pre-PCV13 data suggested that with the case load in the population selected, we had only 63% power to detect a 20% decline in pneumonia admissions in the three years post-PCV13, using an interrupted time series analysis [25]. It is important to undertake power calculations prior to embarking on pneumonia impact evaluations as there is a danger of drawing erroneous conclusions if the study is undertaken but underpowered [26].…”
Section: Discussionmentioning
confidence: 99%
“…This information provides important supportive evidence to recommend the ongoing use of PCV in Laos. However, we were not able to do a hospital administrative review for pneumonia cases post-PCV with a PCV impact evaluation as we had insufficient power to undertake this; a simulation analysis based on pre-PCV13 data suggested that with the case load in the population selected, we had only 63% power to detect a 20% decline in pneumonia admissions in the three years post-PCV13, using an interrupted time series analysis [25]. It is important to undertake power calculations prior to embarking on pneumonia impact evaluations as there is a danger of drawing erroneous conclusions if the study is undertaken but underpowered [26].…”
Section: Discussionmentioning
confidence: 99%